CircCCDC66: Emerging roles and potential clinical values in malignant tumors - Wang, Xiaoxiao; Zhang, Chao; Song, Huangqin; Yuan, Junlong; Zhang, Lei; He, Jiefeng (Frontiers in Oncology, 2023)
Circular RNAs (circRNAs) are endogenous non-coding RNAs (ncRNAs) with a closed-loop structure. In recent years, circRNAs have become the focus of much research into RNA. CircCCDC66 has been identified as a novel oncogenic circRNA and is up-regulated in a variety of malignant tumors including thyroid cancer, non-small cell carcinoma, gastric cancer, colorectal cancer, renal cancer, cervical cancer, glioma, and osteosarcoma. It mediates cancer progression by regulating epigenetic modifications, variable splicing, transcription, and protein translation. The oncogenicity of circCCDC66 suppresses or promotes the expression of related genes mainly through direct or indirect pathways. This finding suggests that circCCDC66 is a biomarker for cancer diagnosis, prognosis assessment and treatment. However, there is no review on the relationship between circCCDC66 and cancers. Thus, the expression, biological functions, and regulatory mechanisms of circCCDC66 in malignant tumor and non-tumor diseases are summarized. The clinical value and prognostic significance of circCCDC66 are also evaluated, which can provide insights helpful to those exploring new strategies for the early diagnosis and targeted treatment of malignancies.